A paradigm of volatile aroma compounds in rice and their product with extraction and identification methods: A comprehensive review. (April 2020) - Verma, Deepak Kumar; Srivastav, Prem Prakash
Graphical abstract: Highlights: Classification, odor description, and chemistry of rice VACs have described. Important information on aroma research of rice and its products have focused. SPME is mostly used as a recent method for extracting rice VACs. GC–MS is frequently used to identify and characterize rice VACs. Abstract: The aroma in rice and its products is one of the important quality characteristics. It is contributed by more than 500 different volatile compounds and the extraction and quantification of aroma compounds are equally essential, determining the threshold of aroma. Till date, a complete review of the aromatic consideration of rice is lacking in the literature. Therefore, the present paper is prepared with the aim of summarizing the data and other significant information in respect of the aroma characteristics of different types of rice and rice products from the early 1980s to 2019. This review discusses all the studies on extraction, isolation, and characterization of volatile aroma compounds (VACs) done in different types of rice and their products which will further help researchers to continue their work on the lacking aspects of rice aroma. A special focus has been given to the 2-AP compound which signified the difference between aromatic and non-aromatic rice cultivars.